Investigating stock market efficiency: a look at OIC member countries - Arshad, Shaista; Rizvi, Syed Aun Raza; Mat Ghani, Gairuzazmi; Duasa, Jarita (Elsevier, 2016)
The tremendous growth of emerging and developing markets bring forth new arenas ofresearch. One such area is the efficiency of stock markets. In light of the Efficient Mar-ket Hypothesis (EMH) several studies have been undertaken over the past two decade,with much focus being on developed markets and certain developing countries. However,a dearth in literature is seen for this niche on Organization of Islamic Conference (OIC)member countries. Following the recent global crisis, attention on emerging and develop-ing markets have increased tremendously, questioning whether these countries’ market areapt in withstanding influxes of capital without crashing. The OIC despite its global presenceand potential has often been criticized about its stock markets, which are marred by under-development and illiquidity. This paper focuses on analysing the weak-form efficiency ofOIC member stock markets to determine their efficiency rankings during different business cycles. Our results are indicative of improving efficiency over the past decade.